Quantitation of delta-crystallin messenger RNA during lens induction in chick embryos. - Shinohara, T (1976)
Embryonic chick cells of the presumptive lens ectoderm are induced to differentiate into a lens by the optic vesicle, an outgrowth from the developing brain. This lens induction involves formation of the lens placode by cell elongation between about 44 and 50 hr of development, followed by invagination of the placode between about 50 and 55 hr of development. The amount of delta-crystallin messenger RNA (mRNA) in heads of embryos between 48 and 72 hr of development was determined by molecular hybridization with [3H]DNA complementary to purified delta-crystallin mRNA. An average of approximately 0.5 pg of delta-crystallin mRNA was found per embryonic head at 48 hr of development. This leads to approximately 265 molecules of delta-crystallin mRNA per lens cell, if one assumes that the mRNA is confined to the lens rudiment, as is indicated by immunofluorescence studies of delta-crystallin performed by other investigators. Pulse-labeling experiments with [35S]methionine indicated that the delta-crystallin mRNA is being translated already at this time. delta-Crystallin mRNA accumulated at an average rate of 1 molecule per cell per minute between 48 and 72 hr of development. Thus, by extrapolation, the initiation of delta-crystallin mRNA accumulation coincides with the initiation of lens placode formation at approximately 43-44 hr of development, which is some 8-9 hr after the initiation of lens induction by the optic vesicle. These data suggest that delta-crystallin synthesis is regulated by the accumulation of delta-crystallin mRNA during lens induction in chick embryos.